G-FEET STICKY HOUSE: THE STRONG AND QUAKERESISTANT HOUSING FOR POST EARTH QUAKE SOLUTION - Rifandi Septiawan Nugroho; Fardilla Rizqiyah; Ekkywona Rumiazizah; Choirur Roziqin; Rizky Darmadi (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2011)
Earthquake is a natural phenomenon occurs in Indonesia. Naturally, earthquake does not kill people, but buildings do. People were killed by the fallen debris of building parts when earthquake occurred. The key to create an entire building lies on the joint system which is why most of building failures occurred on the joint system. Prawiro et all (2010) stated that G-Feet Structural Joint System is the future alternative reversible structural joint system designed based on gecko’s feet concept. The research by Andari et all (2011) found that the joint system was optimum in shear stresses which were mostly created by lateral forces of earthquake. The idea was more lateral forces would lead the joint system to become stickier. Sticky brushes refer to the ability of joint system to easily stick and become strong enough receiving 10 tons/m² load. This can be happened due to the geometry of sticky brushes which are becoming the locking system of the joint system. Therefore, G-Feet Sticky house is supposed to be a new concept of post earthquake houses for the victims. Material selection and 3D computer modelling were used for the final design of G-Feet Sticky Houses to be safely and easily to install. The design is supposed to be useful and helpful especially for the victims as temporary houses which can be modified as the permanent one. The big wall panels are designed for faster construction processwhile the joint system combines the ability of sticky brushes and the geometry of wall panel edge detail.